Highly-sensitive Refractometer Based on a D-shaped Fiber Bragg Grating Integrated into A Loop-mirror Optical Fiber Laser - Pham Thanh, Binh; Nguyen, Thuy Van; Pham, Van Hoi; Bui, Huy; Hoang, Thi Hong Cam; Do, Thuy Chi; Nguyen, Anh Tuan (Communications in Physics, 2021)
In this paper, we report a new type of refractometer based on a D-shaped fiber Bragg grating (FBG) integrated in a loop-mirror optical fiber laser. This proposed sensor is used in wavelength interrogation method, in which the D-shaped FBG is applied as a refractive index (RI) sensing probe and a mirror to select mode of laser. The D-shaped FBG is prepared by the removal of a portion of the fiber cladding covering the FBG by means of side-polishing technique. The D-shaped FBG sensing probe integrated in a loop-mirror optical fiber laser with saturated pump technique, the characteristics of sensing signals have been improved to obtain stable intensity, narrower bandwidth and higher optical signal-to-noise ratio compare to normal reflection configuration. The limit of detection (LOD) of this sensor can be achieved to 2.95 x 10-4 RIU in the refractive index (RI) range of 1.42-1.44. Accordingly, we believe that the proposed refractometer has a huge potential for applications in biochemical-sensing technique.